Bibliometric analysis and network mapping of the scientific literature on the influence of public relations on well-being and happiness. - Rando-Cueto, Dolores; Núñez-Sánchez, José Manuel; Jambrino-Maldonado, Carmen; Iglesias-Sánchez, Patricia Pilar; De-las-Heras-Pedrosa, Carlos (Universitat Autònoma de Barcelona., 2023)
Managing employees’ happiness and well-being as a business strategy offers positive outcomes for companies, as has been widely studied in the scientific literature. In the field of public relations, published studies address these benefits for individuals and collectively, both for the employees themselves (Pérez, 2020) and for the organisation for which they work, whether intangible or tangible (Castro-Martínez and Díaz-Morilla, 2020; Sidney et al., 2017). However, the function of promoting a good working environment is not always attended to in the workplace, nor is it always exclusive to a specific area (Bowen, 2008). In addition to a systematic documentary review, the Web of Science database is used for a bibliometric study and network mapping of the scientific literature, from which articles are extracted for analysis using different bibliographic searches. Based on the information obtained, VOSviewer software is used for the analysis of bibliometric networks by authorship, citation and co-occurrence of keywords in scientific publications. The number of articles published on the management of happiness and wellbeing in organisations as part of their public relations has increased significantly over the last decade, although there has been a notable change in this growth since 2021. According to the research, corporate social responsibility programmes are increasingly considering these aspects as part of their organisational strategy, and departments such as human resources are taking on a greater role in generating a good working environment. This study provides an overview of the international production of scientific publications on the subject of happiness management and organisational well-being from the point of view of public relations. It shows the evolution of scientific activity in terms of the number of works published by area of knowledge and the current trends in terms of authorship, subject matter and repercussion in the scientific field.
Análisis bibliométrico y mapeo de redes de la literatura científica sobre la influencia de las relaciones públicas en el bienestar y la felicidad.
Keywords: Satisfacción en el trabajo; Happiness; Well-being; Bibliometric; Organizations; Public relations